Prevalence and Factors Associated With Burnout of Frontline Healthcare Workers in Fighting Against the COVID-19 Pandemic: Evidence From China - Zhang, Xin; Wang, Jiahui; Hao, Yanhua; Wu, Ke; Jiao, Mingli; Liang, Libo; Gao, Lijun; Ning, Ning; Kang, Zheng; Shan, Linghan; He, Wenfeng; Wang, Yongchen; et al. (Frontiers in Psychology, 2021)
Objectives: The sudden outbreak of the novel coronavirus disease (COVID-19) plunged healthcare workers into warfare. This study aimed to determine the prevalence of burnout and the factors associated with it among frontline healthcare workers fighting COVID-19. Methods: A cross-sectional survey was conducted among COVID-19 frontline healthcare workers in China from 18 February to 4 March, 2020. Finally 1163 healthcare workers were included in the final analysis. Burnout was measured using a 22-item Maslach Burnout Inventory scale (MBI scale). Results: Of the participants, 48.6% suffered from burnout, and 21.8% showed a high degree of burnout. Doctors and nurses showed higher emotional exhaustion (EE) than administrators. Participants who worked continuously for more than 8 hours a day, those who were unable to eat three regular meals, whose daily water intake was no more than 800 ml, who slept for no more than 6 hours, and who were infected or had colleagues who were infected with COVID-19 experienced much higher levels of EE, while those who could adhere to infection control procedures, who were satisfied with their hospital’s infection control measures, and who could receive sufficient psychological crisis intervention reported lower levels of EE. Conclusions: Burnout is prevalent and interventions should be targeted at reducing its occurrence among frontline healthcare workers fighting COVID-19.